Acquired Hemophilia A Presenting as Massive Postoperative Bleeding in a Patient with Oral Squamous Cell Carcinoma - Oba, Susumu; Nakahira, Mitsuhiko; Kogashiwa, Yasunao; Ebihara, Yasuhiro; Sugasawa, Masashi (Case Reports in Otolaryngology, 2020)
Acquired hemophilia A (AHA) is an extremely rare and serious bleeding disorder caused by autoantibodies against coagulation factor VIII (FVIII). Approximately, 10% of patients with AHA have an underlying malignancy. We report on a 46-year-old man with AHA and advanced oral cancer who presented with massive bleeding after surgery. Preoperative blood coagulation tests showed no abnormalities. He underwent radical tumor resection followed by reconstruction using a free rectus abdominal musculocutaneous flap. Massive subcutaneous hemorrhage developed in his neck and abdomen on the first postoperative day. The hemorrhage remained uncontrolled, despite embolization of the responsible vessels. Subsequent laboratory data showed prolonged activated partial thromboplastin time and decreased FVIII levels. On the basis of his clinical course and the presence of the FVIII inhibitor, we speculated that the patient suffered from AHA. We administered recombinant activated factor VII and prednisolone, after which the spontaneous bleeding stopped and the subcutaneous hemorrhage resolved. A review of the literature identified only three previous documented cases of AHA associated with head and neck cancer. This case indicates that AHA should not be ruled out in patients with uncontrolled postoperative bleeding, while attempting to ensure bleeding control and preventing potentially catastrophic fatal consequences.